2015
DOI: 10.1107/s1399004715003521
|View full text |Cite
|
Sign up to set email alerts
|

Structures of theMiddle East respiratory syndrome coronavirus3C-like protease reveal insights into substrate specificity

Abstract: Middle East respiratory syndrome coronavirus (MERS-CoV) is a highly pathogenic virus that causes severe respiratory illness accompanied by multiorgan dysfunction, resulting in a case fatality rate of approximately 40%. As found in other coronaviruses, the majority of the positive-stranded RNA MERS-CoV genome is translated into two polyproteins, one created by a ribosomal frameshift, that are cleaved at three sites by a papain-like protease and at 11 sites by a 3C-like protease (3CL pro ). Since 3CL pro is esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 54 publications
1
88
0
4
Order By: Relevance
“…Each monomer features three domains: domain I (residues 1-97), domain II (residues 98-186), and domain III (residues 202-298). Each of the first two domains exhibits an antiparallel β-barrel structure, which is similar to the 3CL pro s from other coronaviruses (Anand et al, 2002;Needle et al, 2015;Yang et al, 2003). Domain III consists of five α helices and is connected to domain II by a long loop (residues 187-197, loop A in Fig.…”
Section: Overall Structure Of Pedv 3cl Promentioning
confidence: 71%
“…Each monomer features three domains: domain I (residues 1-97), domain II (residues 98-186), and domain III (residues 202-298). Each of the first two domains exhibits an antiparallel β-barrel structure, which is similar to the 3CL pro s from other coronaviruses (Anand et al, 2002;Needle et al, 2015;Yang et al, 2003). Domain III consists of five α helices and is connected to domain II by a long loop (residues 187-197, loop A in Fig.…”
Section: Overall Structure Of Pedv 3cl Promentioning
confidence: 71%
“…Then, the simulation was done by Discovery Studio (Accelrys Inc., San Diego, CA). A Cys at subsite S1 of 3CL pro acts as a nucleophile to cleave substrates by attacking carbonyl carbon of the amide bond between the conserved Gln at P1 and the small amino acids such as Ser, Ala or Gly at P1' (Fan et al, 2004;Needle et al, 2015). Our modelling shows that the g-sulfur of Cys148 forms a covalent bond with the 6d aldehyde carbon and the resulting oxyanion is stabilized by His41 (Fig.…”
Section: In Silico Molecular Docking Of 6d Against Mers-cov 3cl Promentioning
confidence: 83%
“…The homodimeric form of 3CLpro is active in the presence of substrates. The crystal structure of 3CLpro showed that each monomer is composed of three structural domains: domains I and II form a chymotrypsinlike architecture with catalytic cysteine and are connected to a third C-terminal domain via a long loop (Neddle, Lountos, & Waugh, 2015). In the proteolytic site, all 3CLpros prefer glutamine at P1 position and leucine, basic residues, small hydrophobic residues at P2, P3 and P4 positions, respectively (Chuck, Chow, Wan, & Wong, 2011).…”
Section: Introductionmentioning
confidence: 99%